ASPECTS REGARDING THE USE OF COLLABORATORS IN THE CRIMINAL TRIAL - Mircea-Constantin SINESCU; Alin-Sorin NICOLESCU (Challenges of the Knowledge Society)
This work covers the review of the main issues arising in judicial practice with regard to the use of special surveillance or investigation methods, especially the use of undercover investigators and of collaborators, starting from ordering such measures all the way through the limits the intervention of such investigator/collaborator should respect.